ASSESSMENT OF VISUAL POLLUTION IN URBAN SQUARE IN BATNA CITY CENTER (ALGERIA): USING SWOT, AHP, AND QSPM TECHNIQUES - Djelloul Fatima Zohra; Zeraib Salah; Abbas Saliha (International Journal of Innovative Technologies in Social Science, 2025)
Visual pollution is one of the forms of pollution that is no less dangerous than other common types of pollution (such as noise pollution, air pollution, and others). Visual pollution takes many forms, but it shares its essence with regard to its relationship to confusion in the brain’s processing of inconsistent visual inputs, which negatively affects the individual’s health in general, and in particular his mental and psychological health. The present study applies SWOT and QSPM techniques to identify and introduce the most influential factors related to visual pollution in the internal and external environment of Batna city, by assessment the rate of visual pollution in freedom squares. Accordingly, in the SWOT matrix, the strengths, weaknesses, threats and opportunities of these squares were studied, and using expert selection, the AHP method was applied to weigh them. SWOT can be used as an analytical tool for evaluation purposes in the QSPM system. Finally, using the quantitative strategic planning matrix (QSPM), the priorities of the selected strategies were determined, Using the QSPM matrix, the study proposed eight prioritization strategies, which provided the best possible strategy for this square.